Strategi Servis Excellent Pada Bento Kopi Lontar Melalui Analisis 5A+S (Attitude, Attention, Action, Ability, Accountability, Speed/Satisfaction) - Moch Angga Adjie Saputra; Ariyan Alfraita; Fitria Widiyani Roosinda (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to identify and analyze the service excellence strategy at Bento Kopi Lontar through the 5A+S analysis, which includes Attitude, Attention, Action, Ability, Accountability, and Speed/Satisfaction. This research is motivated by the importance of service quality in the food and beverage industry, especially coffee shops, which face intense competition. Therefore, service quality becomes an important factor in creating customer satisfaction and maintaining customer loyalty. This study uses a descriptive qualitative research method with data collection techniques consisting of interviews, observations, and documentation. The research informants include the manager, public relations officer, employees, and customers of Bento Kopi Lontar. The results indicate that the implementation of the 5A+S concept at Bento Kopi Lontar has been carried out quite well. Employees demonstrate friendliness, provide attention to customers, act responsively, possess good service skills, take responsibility in resolving problems, and strive to deliver fast service to increase customer satisfaction. Thus, the implementation of 5A+S plays an important role in supporting the service excellence strategy at Bento Kopi Lontar to create quality service and improve customer satisfaction.